International Congress on Applications of Lasers &Amp; Electro-Optics 2002
DOI: 10.2351/1.5066217
|View full text |Cite
|
Sign up to set email alerts
|

Functionally graded copper – steel using laser engineered net shaping™ process

Abstract: Laser Engineered Net Shaping (LENS) is an emerging Solid Freeform Fabrication (SFF) process capable of producing fully dense metallic parts with complex shapes directly from a computer-aided drawing (CAD) without the need for molding or tooling. The LENS process also shows promise in producing components with graded compositions. One potential application is the production of steel-copper die casting materials. Copper is currently deposited on dies made out of steel to enhance thermal management, however, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…can be used to generate functionally, compositionally-graded material, such as H13 tool steel and A c c e p t e d M a n u s c r i p t copper for thermally-conductive mold dies or implants [120][121][122][123], tungsten carbide-cobalt cerment [46], compositionally-gradient titanium-chromium alloy [124,125], compositionallygradient titanium-vanadium and titanium-molybdenum alloys [126], nickel aluminides [127] and AISI 316L SS-Inconel 718 [128]. Understanding, modeling and optimizing the particle/laser interactions, prior to melt pool entry, is important for furthering DLD technology.…”
Section: Page 23 Of 110mentioning
confidence: 99%
“…can be used to generate functionally, compositionally-graded material, such as H13 tool steel and A c c e p t e d M a n u s c r i p t copper for thermally-conductive mold dies or implants [120][121][122][123], tungsten carbide-cobalt cerment [46], compositionally-gradient titanium-chromium alloy [124,125], compositionallygradient titanium-vanadium and titanium-molybdenum alloys [126], nickel aluminides [127] and AISI 316L SS-Inconel 718 [128]. Understanding, modeling and optimizing the particle/laser interactions, prior to melt pool entry, is important for furthering DLD technology.…”
Section: Page 23 Of 110mentioning
confidence: 99%
“…The technique was proposed in 1987 to develop heat-resistant coatings, but material combinations, such as copper and nickel (Shin et al, 2003), copper and tool steel (Noecker II and DuPont, 2002), and stainless steel and satellite (Iakovlev et al, 2002) have since been demonstrated. Mazumder et al (1999bMazumder et al ( , 2002 have proposed the concept of using multiple material LDMD to control part manufacture to the level of 'designed' microstructures and have described the development of a complete methodology for the design, representation and fabrication of graded materials (Mazumder, 2003).…”
Section: Functional Gradingmentioning
confidence: 99%
“…Together, these two properties imply that SFF processes are subject to very different constraints than traditional material removal-based manufacturing. As has been demonstrated with various (but no single) SFF system, nearly arbitrary product geometries are achievable [1] and parts can be made without hard tooling, raw materials may be more efficiently used than in subtractive processes, mating parts and fully assembled mechanisms can be fabricated in a single step [2], exogenously produced components, such as integrated circuits, can be "dropped in" during fabrication [3], and multiple materials (including, electronic- [4], chemical-, and bio-materials [5][6][7] and even living tissues [8,9]) can be combined to create graded material properties [10][11][12][13] and even complete functional devices [14][15][16]. Furthermore, one or more SFF processes can typically be implemented within a single small workcell [3,14] -compacting enormously what might have once required many separate machines.…”
Section: Introductionmentioning
confidence: 99%